CORRELATION OF ACADEMIC STRESS WITH OLIGOMENORRHEA IN FEMALE MEDICAL STUDENTS - Soewangsa, Queency Amelia; Dewi, Sianty; Dian Putri, Maria Patricia (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: Oligomenorrhea is defined as an irregular menstrual cycle of more than 35 days or only experiencing 4 to 9 menstrual cycles in a year. According to research involving 12,964 women of childbearing age in China, it was found that 1,579 women (12.2%) experienced oligomenorrhea. Risk factors for oligomenorrhea are poor nutritional status, namely BMI < 18.5 or ≥ 25, excessive physical activity, high levels of stress (around 20%), and late age at menarche. Various studies have found a relationship between stress and abnormal menstrual cycles.Objective: To determine the relationship between academic stress and oligomenorrhea infemale students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya, Class of 2019.Method: Analytical observational research with a cross-sectional approach. The population for this research is all 7th-semester female students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya, class of 2019, with a total sample of 32 female students taken using simple random sampling. The independent variable is academic stress while the dependent variable is oligomenorrhea. The research instrument used a questionnaire. Data analysis used the Spearman Rank correlation test.Result: A total of 20 respondents (62.5%) experienced moderate levels of academic stress, 3 respondents (9.4%) experienced low levels of academic stress, and 9 respondents (28.1%) experienced high levels of academic stress. For the menstrual cycle from August to October 2022, 23 female students (71.9%) experienced normal menstrual cycles, and 9 female students (28.1%) experienced oligomenorrhea. The results of the Spearman Rank correlation test obtained a significance value of 0.023.Conclusion: There is a relationship between academic stress and oligomenorrhea in students at the Faculty of Medicine, Widya Mandala Catholic University, Surabaya, Class of 2019.